Publication ethics statement for year 2014 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The publication of an article in this peer reviewed journal is an essential model for the scientific journal Military Technical Courier. It is necessary to agree upon standards of expected ethical behavior for all parties involved in the act of publishing: the author, the journal editor, the peer reviewer and the publisher.